A review of the law and practice relating to the collateralization of carbon assets: a comparison of Indonesia and England - Albert Jonathan Sukardi; Ari Wahyudi Hertanto (The International Journal of Politics and Sociology Research, 2023)
The Republic of Indonesia has promulgated Presidential Regulation Number 98 of 2021 concerning the Implementation of Carbon Economic Value for Achieving Nationally Determined Contribution Targets and Controlling Greenhouse Gas Emissions in National Development as a form of follow-up to Indonesia's commitment to reduce carbon and other greenhouse gas emissions in accordance with the Nationally Determined Contribution commitment under the Paris Agreement. One of the main arrangements is related to carbon unit trading as a market-based mechanism to control climate change. In fact, forest reforestation projects, green and renewable energy, and so on require substantial financing but face problems related to providing guarantees to obtain financing. The author uses a normative juridical research method with a literature study to examine the legal regulation of collateral for carbon units as an object of property collateral. The result of the research shows that the specific regulation related to the guarantee of carbon assets is incomplete but can be applied. The research also shows that there are several alternatives in the more common practice of carbon asset pledging such as pledging receivables generated from carbon trading or pledging carbon unit registry accounts.